Description of the Level of Early Marriage Cases in Langkowala Village Community, Konawe Islands Regency, Southeast Sulawesi - Rusydi, Muh. Kemal Ikhsan; Mutmainah; Wehamali, Elda; Nuraena, Sitti; Tosepu, Ramadhan; Efendy, Devi Savitri; Susanty, Sri (Miracle Journal of Public Health, 2023)
Early marriage is a marriage carried out before the age of 18, occurring during adolescence. Where more than 700 million women alive today were married before the age of majority, namely 18 years. Southeast Sulawesi itself is in the top 10 provinces that have marriage rates among teenagers under 19 years of age, with a percentage of 22.29% of early marriage cases occurring in Southeast Sulawesi. The purpose of writing this article is to describe the number of cases of early marriage that occur in the Langkowala village community, Konawe Islands. The study design used is a descriptive method. The population is teenage couples who have married under the age of 18 years with a total of 39 people. The total sample in the study was 39 people. The results of the data obtained from Langkowala village, West Wawonii District, Konawe Islands are dominated by economic factors which are still low (64.11%), the low level of education of young couples which is only on the average up to middle school level (51.28%), the lack of knowledge about reproductive health for couples who marry young (71.79%), as well as a large number of sexual activities outside of marriage (58.97%). Suggestions, there is a need for more intensive socialization of child protection with the target being parents in the aspects of early marriage on reproductive health as well as the need for adolescent health services to expand coverage to at least a periodic program.